Measuring Multiple Brand Corporate Image of Garuda Indonesia’s Instagram - Henky Ade Moerales (Economics and Business Journal (ECBIS), 2026)
The aviation sector is vital for improving national connections and influencing a nation's reputation. Garuda Indonesia is the national airline of Indonesia that faces the challenge of maintaining the corporate image amid competition and rapid digital innovation. Social media, especially Instagram, has become an important medium to improve digital branding and interact with consumers. This study seeks to analyze the impact of brand performance, brand relationship, and brand personality on corporate image via Instagram as a digital branding platform. This research is using quantitative methodology with survey technique with purposive sampling. Multiple linear regression analysis wasperformed on data of 142 Instagram followers of Garuda Indonesia. The findings indicate that brand performance, brand relationship, and brand personality exert positive and significant influences on corporate image, both individually and collectively. Brand personality was the most influential of these elements. The coefficient of determination (R²) was 0.583, which means that the model explains 58.3% of the variance in corporate image. Results show the relevance of integrating functional, emotional and symbolic dimensions in digital branding, with brand personality being a central factor in shaping corporate image.